2015
DOI: 10.5935/0004-2749.20150022
|View full text |Cite
|
Sign up to set email alerts
|

Blood gas analyzer utility in evaluating oxygen kinetics of the aqueous humor

Abstract: Purpose: To measure the partial pressure of oxygen (PO 2 ) and carbon dioxide (PCO 2 ) and the pH of aqueous humor (AH) and arterial blood samples from rabbits using a blood gas analyzer. Methods: Twenty New Zealand rabbits were anesthetized intramuscularly with ketamine and xylazine and were then allowed to breathe room air. Using a gas blood analyzer, arterial blood and AH samples were analyzed for PO 2 , PCO 2 , and pH. Results: The mean arterial blood pressure was 87.14 ± 15.0 mmHg. The mean blood and AH P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Bacteria transfer from the ocular surface to the intraocular is faced with changes in many environmental factors, such as pH, oxygen concentration, immune response, availability of nutrients, etc. ( Ersan et al, 2015 ; Agujetas et al, 2018 ; Braunger et al, 2023 ), and one change in oxygen concentration is just one of the environmental factors, this condition is not fully representative of the complex ocular surface and intraocular environment. Recent studies also suggest that microaerobic lifestyles are important in host-associated microbial communities and the prevalence of microoxygen environments ( Morris and Schmidt, 2013 ; Pedroza-Dávila et al, 2020 ), so we selected changes in environmental oxygen concentration as the experimental variable.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria transfer from the ocular surface to the intraocular is faced with changes in many environmental factors, such as pH, oxygen concentration, immune response, availability of nutrients, etc. ( Ersan et al, 2015 ; Agujetas et al, 2018 ; Braunger et al, 2023 ), and one change in oxygen concentration is just one of the environmental factors, this condition is not fully representative of the complex ocular surface and intraocular environment. Recent studies also suggest that microaerobic lifestyles are important in host-associated microbial communities and the prevalence of microoxygen environments ( Morris and Schmidt, 2013 ; Pedroza-Dávila et al, 2020 ), so we selected changes in environmental oxygen concentration as the experimental variable.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the AH pH did not differ among the groups, and its values agree with those reported by Pietrowskaa (30) . Changes in the AH pH are related to corneal edema, as a function of the occurrence of tissue hypoxia and the inefficiency of the endothelial pumps (31) .…”
Section: Discussionmentioning
confidence: 99%